ANALISIS KOMUNIKASI MATEMATIS SISWA KATEGORI RENDAH DITINJAU DARI TIPE KEPRIBADIAN ISTJ - Agustina, Lady; Khamdani, Yahya; Galatea, Chusnul Khotimah (Kadikma, 2024)
The aim of this research is to describe mathematical communication based on the ISTJ personality type. This type of research uses descriptive qualitative. The subjects in this research were two students who had high mathematics abilities, two students with moderate mathematics abilities, and two students with low mathematics abilities. On the ISTJ personality type as a research subject. ISTJ personality type students are in the low category of mathematical ability, where both have equivalent mathematical communication abilities. Both of them only fulfill 3 indicators of mathematical communication, namely being able to express mathematical ideas, understand mathematical problems, and use mathematical symbols. Furthermore, students with the ISTJ personality type are in the moderate category of mathematical ability, where subject 1 meets 3 indicators of mathematical communication, while subject 2 meets 4 indicators of mathematical communication in each question. Furthermore, students with the ISTJ personality type are in the high category of mathematical ability, where both have equivalent mathematical communication abilities. It is good to fulfill all mathematical communication indicators